Heterogeneous agroecosystems support high diversity and abundance of trap‐nesting bees and wasps among tropical crops - Coutinho, Jeferson G. E.; Angel‐Coca, Catalina; Boscolo, Danilo; Viana, Blandina F. (Biotropica, 2020)
Land‐use intensification for agricultural purposes modifies the structure of natural environments in various ways and at different spatial scales. These modifications can affect ecological processes and the community structure of multi‐environment users such as solitary bees and wasps. Understanding the role of distinct habitat descriptors in promoting such changes is one of the major challenges of empirical studies. In this study, we use a multi‐scale approach to evaluate how landscape compositional and configurational heterogeneity, vegetation structural complexity, and the proportion of agricultural landscape composition affect communities of bees and wasps that nest in pre‐existing cavities in remnants of native vegetation bordering agroecosystems. We selected 25 sampling points along a gradient of amount of surrounding agriculture and landscape diversity within natural physiognomies located in Chapada Diamantina, Bahia, Brazil. Through model selection using Akaike's information criterion, we verified the complementary roles of landscape heterogeneity and local vegetation in structuring these hymenopteran communities. Abundance in the groups showed different tendencies depending on the descriptors employed, pointing to the importance of evaluating within‐group specificity. Furthermore, bees and wasps presented differential responses to landscape composition, but they did not differ in relation to configurational complexity. In more heterogeneous landscapes or sites with more complex local vegetation, the proportion of agriculture had a positive influence on the response evaluated. Efficient management of agricultural landscapes therefore requires increased landscape heterogeneity and conservation or restoration of native vegetation remnants at the local scale. Resumo A intensificação do uso do solo para fins agrícolas modifica a estrutura dos ambientes naturais de várias maneiras e em diferentes escalas espaciais. Essas modificações podem afetar processos ecológicos e a estrutura das comunidades de animais que usam múltiplos hábitats, como abelhas e vespas solitárias. Compreender o papel das variáveis que descrevem o hábitat na mudança da estrutura das comunidades é um dos principais desafios dos estudos empíricos. Neste estudo, usamos uma abordagem em várias escalas espaciais para avaliar como a heterogeneidade da composição e da configuração da paisagem, a proporção de agricultura, bem como a complexidade estrutural da vegetação afetam comunidades de abelhas e vespas que nidificam em cavidades pré‐existentes em remanescentes de vegetação nativa em agroecossistemas. Foram selecionados 25 pontos amostrais ao longo de um gradiente de proporção de agricultura e diversidade da paisagem em fitofisionomias naturais localizadas na Chapada Diamantina, Bahia, Brasil. Através da seleção de modelos usando o Critério de Informação de Akaike (AIC), verificamos os papéis complementares da heterogeneidade da paisagem e vegetação local na estruturação dessas comunidades de himenópteros. A abundância nos grupos mostrou tendências diferentes dependendo dos descritores empregados, apontando a importância de avaliar a especificidade dentro do grupo. Além disso, abelhas e vespas apresentaram respostas diferentes à composição da paisagem, mas não diferiram em relação à complexidade da configuração. Em paisagens mais heterogêneas ou locais com vegetação local mais complexa, a proporção da agricultura teve uma influência positiva na resposta avaliada. Portanto, o manejo eficiente de paisagens agrícolas requer maior heterogeneidade da paisagem e conservação ou restauração de remanescentes de vegetação nativa em escala local.